Algebraic Thought Process in Solving Problems in Linear Program Materials Reviewed from Learning Motivation - Arie Purwa Kusuma; S B Waluya; S Mariani; Rochmad Rochmad (Universitas Negeri Semarang, 2021)
The ability to think algebra is the ability to generalize the experience of numbers and calculations, find concepts of patterns and functions, and form ideas using symbols. This study aims to describe how the algebraic thinking process of STKIP Kusuma Negara students in Linear Program material. The subject of research is a semester V student of mathematics education who is studying linear program course Year 2020/2021. The data used in this study are the results of questionnaires, test results, and interviews. Taking the subject using purposive sampling techniques. The main instruments are researchers and auxiliary instruments are written test results and interview results on mathematical problems. Data analysis techniques include: (1) data description of written test results and interview results; (2) analyzed from written tests and interview results; (3) then conclude. The data validity test is done by time triangulation. The results of the study lead to the higher the independence of learning owned by students, the higher the ability to think algebra. Students with high algebraic thinking skills have fulfilled every indicator of algebraic thinking, namely being able to generalize, abstract, model, think dynamically and be able to organize. Students with moderate algebraic thinking ability are only able to win three indicators, namely being able to generalize, abstract, and model. While students with low algebraic thinking ability some can abstract and model.